PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS KONTEKSTUAL PELAJARAN MATEMATIKA MATERI BANGUN DATAR SEKOLAH DASAR - Ismar, Ismardianto; Indiri Astuti; Dede Suratman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
The flat shape material in elementary school mathematics lessons is abstract, making it difficult for students to understand in their learning. So media is needed that es the material into concrete by connecting the real life context (contextual) of students. The aim of this research is to develop media in the form of contextually based interactive multimedia to help students construct their knowledge in overcoming these problems so that their learning outcomes increase. The research carried out was Research and Development (R&D) using the ADDIE model. Based on the results of data analysis from expert tests, media experts received a score of 4.4 in the very appropriate category, design experts received a score of 4.5 in the very appropriate category and material experts received a score of 4.5 in the very appropriate category. Furthermore, research at the implementation stage in the learning process obtained an increase in learning outcomes where in the pretest the learning outcomes were an average of 50.71, increasing in the posttest with an average result of 77.67. Thus, it is concluded that contextually based interactive multimedia can improve students' learning outcomes in mathematics lessons on plane material.visualiz